Double Negative T Regulatory Cells: An Emerging Paradigm Shift in Reproductive Immune Tolerance? - Bafor, Enitome E.; Valencia, Julio C.; Young, Howard A. (Frontiers in Immunology, 2022)
Immune regulation of female reproductive function plays a crucial role in fertility, as alterations in the relationship between immune and reproductive systems result in autoimmune subfertility or infertility. The breakdown of immune tolerance leads to ovulation dysfunction, implantation failure, and pregnancy loss. In this regard, immune cells with regulatory activities are essential to restore self-tolerance. Apart from regulatory T cells, double negative T regulatory cells (DNTregs) characterized by TCRαβ+/γδ+CD3+CD4–CD8– (and negative for natural killer cell markers) are emerging as effector cells capable of mediating immune tolerance in the female reproductive tract. DNTregs are present in the female reproductive tract of humans and murine models. However, their full potential as immune regulators is evolving, and studies so far indicate that DNTregs exhibit features that can also maintain tolerance in the female reproductive microenvironment. This review describes recent progress on the presence, role and mechanisms of DNTregs in the female reproductive system and immune regulation and tolerance. In addition, we address how DNTregs can potentially provide a paradigm shift from the known roles of conventional regulatory T cells and immune tolerance by maintaining and restoring balance in the reproductive microenvironment of female fertility.